Aspectos epidemiológicos do carcinoma basocelular dos pacientes operados em hospital de referência de câncer no Estado da Paraíba entre os anos 2009 a 2011 - Andrade, Zuleika Maria Vieira de (2013)
Basal Cell Carcinoma (BCC) is the most common malignancy in humans corresponds to 75% of epithelial malignant tumors. Its incidence is increasing around the world, generating significant burden to the health care system and configuring it as a public health problem. It lies mainly on the face and fair-skinned individuals, involves those over 40 years of age, with a history of exposure to sunlight. We analyzed medical records of all patients diagnosed with BCC in the pathology laboratory of a cancer referral hospital in the state of Paraiba, during the period of 2009 to 2011, with the purpose of analyzing its distribution according to gender, age, location of the tumor, histological subtype, situation of surgical margins, size of the lesions and the origin of the patients. We carried out descriptive analysis of the main variables included in the study, qui-square test, and logistic regression models to identify possible risk factors. The cases were distributed geographically according to the municipality of residence. Along the study period, 3,088 patients were identified with BCC, 48.8% female and 51.52% male. Most of the tumors were located in the head/neck (85.1%), followed by the trunk (10.2%), upper (3.01%) and lower limbs (1.04%); 87.6% were located in the photoexposed areas and only 12.4% in not photoexposed areas. In relation to the location on the head, 33.6% were located in the nose, followed by malar region (23.7%). The nodular subtype was the most frequent (69%), followed by surface type (16%), sclerodermiform (6%), Pigmented (4%) and metatypic (2%). The age group most affected was between 70 to 80 years (26%). Most of the injuries were classified as small, with free surgical margins. A total of 56% of the patients was coming from Zona da Mata region. In bivariate logistic regression models, women had 2.4 times higher risk of developing BCC. The higher age group (OR=5.21) and the origin of Borborema mesoregion (OR=3.88) had significantly higher chance. In the multiple regression mode by including variables that showed statistical significance in bivariate model, showed that the variables Borborema mesoregion (OR=4.88), age ¿ 60 years (OR=5.16) and females (OR=1) remained significant. In this study, we found that the BCC was more frequent in males, above 60 years of age, located in the head, nodular histological type, small size, with free surgical margins and coming from Zona da Mata region. More studies are needed to assess risk factors such as skin color, the profession, sun-exposed activities and family history.